Iron Carbides: Control Synthesis and Catalytic Applications in COx Hydrogenation and Electrochemical HER. Issue 50 (22nd July 2019) - Li, Siwei; Yang, Jinghe; Song, Chuqiao; Zhu, Qingjun; Xiao, Dequan; Ma, Ding
Abstract: Catalytic transformation of CO x ( x = 1, 2) with renewable H2 into valuable fuels and chemicals provides practical processes to mitigate the worldwide energy crisis. Fe‐based catalytic materials are widely used for those reactions due to their abundance and low cost. Novel iron carbides are particularly promising catalytic materials among the reported ferrous catalysts. Recently, a series of strategies has been developed for the preparation of iron carbide nanoparticles and their nanocomposites. Control synthesis of FeC x ‐based nanomaterials and their catalytic applications in CO x hydrogenation and electrochemical hydrogen evolution reaction (HER) are reviewed. The discussion is focused on the unique catalytic activities of iron carbides in CO x hydrogenation and HER and the correlation between structure and catalytic performance. Future synthesis and potential catalytic applications of iron carbides are also summarized. Abstract : Iron carbide is a type of novel Fe‐based material and widely used in the field of catalysis. Control synthesis of iron carbides and their applications in catalytic CO x hydrogenation and electrocatalytic hydrogen evolution reaction are reviewed.